Parti Islam Semalaysia (PAS) dalam kerjasama politik di Malaysia, 1999-2015 / Mohd Izani Mohd Zain - Mohd Izani, Mohd Zain (2017)
The research aims to understand better the nature of Parti Islam SeMalaysia’s (PAS) political cooperation between 1999 and 2015, through alliances of Barisan Alternatif (BA), Pakatan Rakyat (PR), Kelab Penyokong PAS (KPP) and Dewan Himpunan Penyokong PAS (DHPP). In doing so, PAS’ approach, development and implication in the political cooperation are investigated to determine the nature of its participation. Oral history method was conducted and primary sources, such as documents and minutes of meeting, were referred to in order to obtain data. Findings reveal that PAS adopts the concept of Tahaluf Siyasi as its political cooperation approach with a view to achieve victory for Islam and the party’s endeavours. The research also discovers that PAS’ political cooperation within the time frame of the study has explored a new type of alliance which supersedes the election but places focus on mutually beneficial issues, based on the adoption of the concepts of tolerance, democratic and inclusive. PAS also finds itself having to face the implications of its political cooperation, when there appears to be a head-on collision between the concept of Tahaluf Siyasi which it embraces, and that of the notions of tolerance, democratic and inclusive, which are a result of the cooperation. The findings are corroborated through the turbulence and dilemma that the party faces, such as when it finds itself having to balance its political objective with that of the party’s original goals, managing democracy beyond the election and exploring multiracial political stance. The crux of the research is the finding that PAS’ political cooperation remains within the realm of coalition of convenience, and does not look like it is anywhere near a coalition of commitment, defined as cooperation which is based on high commitment amongst its members.